PENGARUH KETEBALAN BATU ANDESIT TERHADAP KELUARAN TERMOELEKTRIK - Ary Akbar Nugraha; Massus Subekti; Imam Arif Rahardjo (Fakultas Teknik Universitas Negeri Jakarta, 2018)
Abstract. This research aimed to create and utilize video-based learning media on motor control course and also to determine whether the video-based learning media on motor control course is effective or not. The making of the video-based learning media using several stages, namely, literature study, analysis needs, product planning, product making, instrument making feasibility and feasibility studies that are conducted by the experts, media specialists and students in order to determine the feasibility of the media created. Furthermore, to test the effectiveness of video-based learning media on motor control course, students are given the post- test questions that the validity and reliability have previously been tested by using an experimental model. The results of the feasibility test got a score > 80%, subject experts got a score of 94.23%, media experts 91,66%, and students 86.13%. The results of the feasibility test obtained, video-based learning media on motor control course is said to be very good and fit for use as a media of learning. The average value of students post test using a video-based learning media is 83, while students who do not use a video-based learning media have an average of 80.56. These data showed that value of post test results of motor control course that uses video-based learning media is higher than value of post test results that does not use a video-based learning media. The difference in post test results show that a video-based learning media on motor control course is an effective media of learning. Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh ketebalan batu andesit terhadap keluaran termoelektrik. Penelitian ini menggunakan metode penelitian eksperimen dengan pendekatan kuantitatif. Subjek penelitian ini ialah ketebalan batu andesit. Ketebalan batu andesit yang digunakan yaitu ketebalan 1 cm, 2 cm, dan 3 cm. Penelitian ini dilakukan pengujian laju kalor konduksi dan keluaran termoelektrik berdasarkan ketebalan batu andesit. Teknik analisis data yang digunakan yaitu analisis deskriptif dengan teknik pengumpulan data yaitu observasi laboratorium dan observasi lapangan. Hasil penelitian ini menunjukkan bahwa batu andesit ketebalan 1 cm menghasilkan laju kalor konduksi tertinggi dibandingkan ketebalan 2 cm dan 3 cm. Begitu juga dengan keluaran yang dihasilkan termoelektrik. Batu andesit ketebalan batu 1 cm menghasilkan keluaran paling besar dibandingkan ketebalan batu 2 cm dan 3 cm. Tegangan keluaran V0 (tanpa beban) dan V1 (dengan hambatan 100 ohm) yang dihasilkan termoelektrik pada ketebalan batu 1 cm berturut- turut sebesar 1.40 V dan 1.08 V, ketebalan batu 2 cm sebesar 1.37 V dan 0.98 V, dan ketebalan batu 3 cm sebesar 1.22 V dan 0.94 V. Berdasarkan hasil data pengujian tersebut dapat disimpulkan bahwa ada pengaruh ketebalan batu andesit terhadap keluaran termoelektrik.